ḤUKMU AL-WAQF ‘ALĀ MARĀKIZ MU‘ĀLAJATI AL-MUDMINĪN WA TA’ḤĪLIHIM FĪ AL-FIQH AL-ISLĀMĪ - Hammad, Hamza Abed AlKarim (Jurnal Al-Dustur, 2026)
This research aims to identify the ruling on Waqf on Centers for the treatment and rehabilitation of addicts in Islamic jurisprudence, the research was based on the descriptive analytical approach and then the Fiqh study of the subject, and the research concluded that it is permissible to Waqf on Centers for the treatment and rehabilitation of addicts, based on a number of evidence, including: this kind of waqf is a form of doing good, and the Holy Quran has urged to do good, Moreover, what are addiction treatment centers can be said to be a special type of hospitals specialized in the treatment of certain diseases, and not one of the jurists has stipulated the permissibility of Waqf on hospitals. In addition to the fact that the moratorium on addiction treatment and rehabilitation centers is in line with the fact that the origin of the detainee must be on the side of obedience and righteousness, also, to the fact that the Waqf on the Treatment Centers for addicts and their rehabilitation is certified by the correct measure of Waqf, which is its compliance with the teachings of the Islamic Sharia and the absence of disobedience to the entity on which the Waqf will be placed, it is also one of the purposes of Islamic law: the Waqf on the Treatment Centers for addicts and their rehabilitation fulfills the purpose of protecting the soul and the mind, which are two of the five necessities.